1991
DOI: 10.1161/01.cir.83.3.1015
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarct size-limiting effect of ischemic preconditioning was not attenuated by oxygen free-radical scavengers in the rabbit.

Abstract: Ischemic preconditioning delays ischemic myocardial necrosis regardless of myocardial xanthine oxidase content. Free radicals are unlikely to have a major role in the mechanism of the preconditioning in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 23 publications
0
29
0
2
Order By: Relevance
“…In keeping with these results, Tritto and coworkers (60) noted that a brief (5-min) exposure of isolated rabbit hearts to a free radical-generating solution resulted in subsequent reduction of infarct size. In contrast, Iwamoto et al (61) were unable to abolish the protective effects of ischemic preconditioning against infarction with either SOD alone or SOD and catalase in open-chest rabbits. Richard et al (62) were also unable to block preconditioning against infarction with MPG in openchest rats.…”
Section: Discussionmentioning
confidence: 87%
“…In keeping with these results, Tritto and coworkers (60) noted that a brief (5-min) exposure of isolated rabbit hearts to a free radical-generating solution resulted in subsequent reduction of infarct size. In contrast, Iwamoto et al (61) were unable to abolish the protective effects of ischemic preconditioning against infarction with either SOD alone or SOD and catalase in open-chest rabbits. Richard et al (62) were also unable to block preconditioning against infarction with MPG in openchest rats.…”
Section: Discussionmentioning
confidence: 87%
“…31 P NMR spectra were obtained at 109. 16 MHz using a JEOL GSX 270 wide-bore NMR spectrometer (6.35 tesla field strength; Nihon Denshi, Tokyo, Japan). The proton signal from the heart was used for shimming.…”
Section: P Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
“…However, in the present study neither 5-HD nor NAC inhibited the cardioprotection induced by IPC, suggesting that IPC is not mediated through the mitoKATP channel opening or ROS production during the preconditioning period. Several investigators have also documented that the administration of 5-HD [13][14][15] and ROS scavengers 16,17,26 could not cancel the cardioprotective effects of IPC. Lim et al have indicated that DZ and 5-HD have additional effects on mitochondrial function, independently of any effects on mitoKATP channels.…”
Section: Involvement Of Mitokatp Channels and Ros In Dz-and Ipc-inducmentioning
confidence: 99%
See 1 more Smart Citation
“…as to whether the experiments are performed under in vitro or in vivo conditions, the dose and route of administration of the antioxidant applied, as well as the intensity of the preconditioning stimulus (i.e. the duration and number of the preconditioning occlusions) [57,58,59,60] which may substantially determine the signaling pathways which lead to cardioprotection [61]. In addition, the possible trigger or mediator role of ROS in PC and their relation to the mitoK ATP channels, is also not fully elucidated [62,63].…”
Section: The Role Of Reactive Oxygen Species In Preconditioningmentioning
confidence: 99%